Road Traffic Accident and its Characteristics in Kathmandu Valley - Gautam, Sanjay; Joshi, Bandana (International Journal on Engineering Technology, 2024)
Road Traffic Accident (RTA) is defined as an accident, which takes place on the road between two or more objects, in which one is any kind of moving vehicle and the other is another vehicle, pedestrian, animal, or stationary object. The major scope of this study is to analyze factors influencing road accident in Kathmandu Valley (i.e. Kathmandu, Bhaktapur and Lalitpur district), Nepal. Data used in this research were collected from Kathmandu Valley Traffic Police for FY 2070/71 to 2079/80 of the Nepalese Calendar. Both quantitative and qualitative analysis of data was performed. There were several variables used to analyze the collected data including age of driver, gender of driver, fatality rate, time of accident, reason of accident, type of vehicle involved in an accident. The result of analysis shows that 76752 accidents took place in FY 2070/71 to 2079/80. Vehicles most involved in accidents were motorcycle/scooters (54675) followed by car/jeep/van (46928) (both combining, contributing total of almost 75%). The number of male deaths was three times more than that of female death, (i.e. male death victims were 1360 and female were 409). Based on the age, 55% of total death victims were of age group 16-35 i.e. 969 deaths were of this age group. Largest number of accidents (31473) took place during 12:00-18:00 and the major cause of accidents was reckless driving. Other cause of road accident includes over speeding, alcohol consumption, pedestrian’s carelessness, road condition, physical and mental condition of driver. The objective of this research is to identify the trend of accident, investigate the possible causes of accidents, and suggest countermeasures for reducing road traffic accident.